2022
DOI: 10.3389/fevo.2022.963116
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic potential and allelochemical composition in different soil layers of Rhododendron delavayi forest, southwest China

Abstract: Forests habituated by Rhododendron delavayi often lack understory vegetation, which could possibly be a consequence of allelopathy. It is a phenomenon by virtue of which certain plant species produce allelochemicals that affect the growth and behavior of surrounding plants. To elucidate the allelopathic potential and allelochemicals present in the different layers of a R. delavayi forest, extracts obtained from three layers of the forest were used for seed germination bioassays and gas chromatography-mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Previous research found that at certain concentrations, protocatechuic acid and ferulic acid could significantly reduce the early growth parameters of seeds and seedlings (Fu et al, 2019;Šćepanović et al, 2022). We found high levels of protocatechuic acid and ferulic acid, confirming the results of a previous study on the phenolic acid content of litter (Quan et al, 2022). However, since litter decomposes over time, the chemical composition and quantity of produced allelochemicals change to varying degrees due to physical and chemical changes in the environment (Blum et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Previous research found that at certain concentrations, protocatechuic acid and ferulic acid could significantly reduce the early growth parameters of seeds and seedlings (Fu et al, 2019;Šćepanović et al, 2022). We found high levels of protocatechuic acid and ferulic acid, confirming the results of a previous study on the phenolic acid content of litter (Quan et al, 2022). However, since litter decomposes over time, the chemical composition and quantity of produced allelochemicals change to varying degrees due to physical and chemical changes in the environment (Blum et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Baili Rhododendron National Forest Park (abbreviated as Baili Rhododendron) is the largest subtropical evergreen rhododendron forest in the world and is located in southwest China. However, due to the number of tree species is relatively small, weak forest ecological stability, and natural regeneration obstacles, litter has become an important part of forest stand management [ 13 ]. Through field investigation and research, the team found that there was a thick litter and humus layer under the rhododendron forest enriched in decomposed substances, such as lignin and cellulose, and rich in organic acids and allelopathic substances, which affected the natural regeneration of the rhododendron forest to a certain extent [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination is the most important phase of the plant life cycle and is inhibited or delayed by allelochemicals [ 20 ]. In other studies, phytotoxic effects have been found to reduce the speed of seed germination [ 6 , 21 , 22 ]. It has been shown that the inhibition of seed germination is stronger in dicotyledonous plants than in cereals.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some authors have demonstrated that, at some concentrations, protocatechuic acid and ferulic acid can significantly reduce the parameters of early growth of seeds and seedlings [ 22 , 24 ]. The dominance of protocatechoic acid observed by us here in the leaf litter of Q. rubra confirms the results of the previous studies.…”
Section: Discussionmentioning
confidence: 99%